2020
DOI: 10.1039/c9nr07977g
|View full text |Cite
|
Sign up to set email alerts
|

Transverse lipid organization dictates bending fluctuations in model plasma membranes

Abstract: Neutron spin-echo (NSE) spectroscopy to measure the bending fluctuations of large unilamellar vesicles having an asymmetric transbilayer distribution of high- and low-melting lipids. Image by Kayle Kathleen Marie Gorospe of the University of Windsor Science Meets Art program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 62 publications
2
27
2
Order By: Relevance
“…There is evidence that a non-zero leaflet tension could explain the surprising increase in bending rigidity observed in asymmetric vesicles prepared with the phase transfer technique [67]. A similar asymmetry-induced increase in the bending modulus was also reported in vesicles prepared using cyclodextrin-mediated lipid exchange [101]. These observations suggest that asymmetric model membranes in vitro likely harbor differential stress irrespective of how they are prepared.…”
Section: Molecular Dynamics (Md) Simulations Used To Model Asymmetric Membranessupporting
confidence: 54%
“…There is evidence that a non-zero leaflet tension could explain the surprising increase in bending rigidity observed in asymmetric vesicles prepared with the phase transfer technique [67]. A similar asymmetry-induced increase in the bending modulus was also reported in vesicles prepared using cyclodextrin-mediated lipid exchange [101]. These observations suggest that asymmetric model membranes in vitro likely harbor differential stress irrespective of how they are prepared.…”
Section: Molecular Dynamics (Md) Simulations Used To Model Asymmetric Membranessupporting
confidence: 54%
“…We therefore directly estimate the effective bending modulus, κ, which contains the effects of internal lipid monolayer dissipation. These effects are highly sensitive to the differences in surfactant properties and environment 19 and can provide mechanistic insights into EVALI pathology.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Other applications of NSE involve the utilization of neutron isotope sensitivity to investigate the dynamics of selective features within lipid membranes. For example, Rickeard et al (2020) used asymmetric lipid membranes with one of their bilayer leaflets selectively deuterated to investigate the effect of asymmetry and leaflet coupling on membrane bending fluctuations. Surprisingly, they found that asymmetric membranes possessed a larger bending modulus than symmetric bilayers with the same average lipid composition, a result that was uniquely enabled by NSE.…”
Section: Neutron Spin Echomentioning
confidence: 99%
“…Results from neutron scattering experiments have produced new insights, not only with regard to the material properties of membranes (e.g., bending rigidity), but also pertaining to their physical properties and how they relate to biological function. These insights have led to a better understanding of proteinlipid interactions, lipid domain formation and size, and PM asymmetry (Clifton et al, 2013;Marquardt et al, 2015;Heberle et al, 2016;Nickels et al, 2017;Rickeard et al, 2020).…”
Section: Introductionmentioning
confidence: 99%